The Common C49620T Polymorphism in the Sulfonylurea Receptor Gene SUR1 (ABCC8) in Patients with Gestational Diabetes and Subsequent Glucose Metabolism Abnormalities. (15th August 2012) - Molęda, Piotr; Bińczak-Kuleta, Agnieszka; Homa, Katarzyna; Safranow, Krzysztof; Celewicz, Zbigniew; Syrenicz, Anhelli; Stefański, Adam; Fronczyk, Aneta; Majkowska, Lilianna
Abstract : Aim . The aim of this study is to investigate the relationship between the common C49620T polymorphism in the sulfonylurea receptor (SUR1) gene and glucose metabolism, β -cell secretory function and insulin resistance in women with a history of gestational diabetes (GDM). Material and Methods . Study group included 199 women, diagnosed GDM within the last 5–12 years and control group of comparable 50 women in whom GDM was excluded during pregnancy. Blood glucose and insulin levels were measured during oral glucose tolerance test. Indices of insulin resistance (HOMA-IR) and β -cell function (HOMA %B) were calculated. In all patients, the C49620T polymorphism in intron 15 of the SUR1 gene was determined. Results . The distribution of the studied polymorphism in the two groups did not differ from each other ( χ 2 = 0.34, P = 0.8425 ). No association between the distribution of polymorphisms and coexisting glucose metabolism disorders ( χ 2 = 7, 13, P = 0, 3043 ) was found. No association was also observed between the polymorphism and HOMA %B or HOMA-IR. Conclusions . The polymorphism C49620T in the SUR1 gene is not associated with insulin resistance and/or insulin secretion in women with a history of GDM and does not affect the development of GDM, or the development of glucose intolerance in the studied population.